MENAKAR INTEGRASI ISLAM DAN ILMU PENGETAHUAN PADA SEKOLAH ISLAM TERPADU - Achmad Faqihuddin; A Toto Suryana Afriatien (Taklim : Jurnal Pendidikan Agama Islam, 2021)
The emergence of Integrated Islamic Schools adds to the treasures for the development of Islamic education in Indonesia. Prior to the emergence of Integrated Islamic Schools, educational institutions in Indonesia consisted of madrasas, public schools and Islamic boarding schools. The existence of Integrated Islamic Schools brings different colors and characteristics when compared to madrasas and pesantren. Integrated Islamic Schools combine religious education which is the hallmark of Islamic boarding schools and modern education which is the hallmark of public schools. The concept of integration is built by combining religious education and general education in one curriculum. The subjects and coaching activities presented are integrated with each other with Islamic values. This study uses a qualitative approach. The results of the study indicate that the concept of integration or integration between Islam and science in Integrated Islamic schools has been contained in the curriculum. However, the limitations of learning resources and teaching resources that can integrate Islam and science are a challenge in their efforts to implement the concept of integration in the Integrated Islamic School. So that the process of Islamization of subjects and training of teaching resources should continue to be carried out to realize an Integrated Islamic School that is in line with the concept of integration.Keywords : Islamic Education, Islamization of Knowledge, Integrated Islamic School